"Dynamic Dualism": Kurth and Riemann on Music Theory and the Mind. (9th December 2019) - Tan, Daphne
Abstract: This article examines Ernst Kurth's critical engagement with the ideas of Hugo Riemann and his eventual reformulation of harmonic dualism in dynamic terms. The principle of "dynamic dualism" appears most cogently in Musikpsychologie ([1931] 1947). After discussing the broader psychological movement within which this book emerged, I outline the aims and audience of Musikpsychologie and provide a detailed discussion of the dynamic dualism Kurth articulates therein. I then return to the origin of Kurth's fascination with dualism, namely to Riemann, tracing points of intersection between the two figures across several decades. I suggest that Kurth's displeasure with Riemann's theories is symptomatic of a broader philosophical disagreement over the explanatory power of music theory and its relation to psychology at the time.